Identification of recurrent regions of chromosome loss and gain in vestibular schwannomas using comparative genomic hybridisation. Issue 11 (19th November 2003) - Warren, C; James, L A; Ramsden, R T; Wallace, A; Baser, M E; Varley, J M; Evans, D G
Abstract : Background: Schwannomas are benign tumours of the nervous system that are usually sporadic but also occur in the inherited disorder neurofibromatosis type 2 (NF2). The NF2 gene is a tumour suppressor on chromosome 22. Loss of expression of the NF2 protein product, merlin, is universal in both sporadic and NF2 related schwannomas. The GTPase signalling molecules RhoA and Rac1 regulate merlin function, but to date only mutation in the NF2 gene has been identified as a causal event in schwannoma formation. Methods: Comparative genomic hybridisation (CGH) was used to screen 76 vestibular schwannomas from 76 patients (66 sporadic and 10 NF2 related) to identify other chromosome regions that may harbour genes involved in the tumorigenesis. Results: The most common change was loss on chromosome 22, which was more frequent in sporadic than in NF2 related tumours. Importantly, eight tumours (10%) showed gain of copy number on chromosome 9q34. Each of the two NF2 patients who had received stereotactic radiotherapy had non-chromosome 22 changes, whereas only one of eight non-irradiated NF2 patients had any chromosome changes. Three tumours had gain on 17q, which has also been reported in malignant peripheral nerve sheath tumours that are associated with neurofibromatosis type 1. Other sites that were identified in three or fewer tumours were regions on chromosomes 10, 11, 13, 16, 19, 20, X, and Y. Conclusions: These findings should be verified using techniques that can detect smaller genetic changes, such as microarray-CGH.